EVALUATION OF ANTIBIOTIC USAGE IN ISKEMIC STROKE PATIENTS WITH INFECTIONS IN RSUP DR. KARIADI SEMARANG PERIOD 2018 - Shafa Nahdah Wibowo; Trianggoro Budisulistyo; Endang Sri Sunarsih; Yora Nindita (Jurnal Kedokteran Diponegoro, 2021)
Abstract Background: According to WHO stroke is the second leading cause of death in the world. Ischemic stroke is the type of stroke with the highest population reaching (80%). Data at RSUP Dr. Kariadi in 2015 showed that the most common complication in stroke was infection (37.9%). The most common cause of infection was bacteria with antibiotics as the main therapy. It is necessary to monitor the use of antibiotics due to increased cases of antibiotic resistance. Objective: To determine the rationality of antibiotic use in ischemic stroke patients with infections in RSUP Dr. Kariadi Semarang Period 2018..